DISEMINASI INFORMASI MITIGASI GEMPA BUMI DAN TSUNAMI BERBASIS KOMUNIKASI RISIKO MELALUI VIDEO ANIMASI BMKG - Andriana, Amanda; Yusalina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the importance of disaster information dissemination and risk communication in enhancing public understanding and preparedness, particularly through digital media such as educational videos produced by the Meteorological, Climatological, and Geophysical Agency (BMKG). This study aims to analyze how information dissemination and risk communication processes are represented in animated video content on earthquake and tsunami mitigation. The study employs the theoretical frameworks of information dissemination and risk communication using a qualitative approach through narrative message analysis and in-depth interviews. The findings show that BMKG delivers information through an educational visual and narrative approach by emphasizing hazard visualization, simplification of scientific concepts, and the use of language that does not provoke panic. In addition, risk communication is carried out by building awareness without generating excessive fear and emphasizing appropriate mitigation actions for the public.